UiTM Sarawak Conference 2008 was a success - Ng, Kui Choo; Aba Ibrahim, Nurhani (Universiti Teknologi MARA, Sarawak, 2009)
As Malaysia joins the rest of the world in moving towards a knowledge-based economy, its main responsibility lies in the development of human capital to produce an adequate supply of intellectual and skilled workforce. UiTM as an institution of higher learning has an important role to play in providing the professional manpower to meet the human resource needs of the country. This was emphasised by YB Datin Fatimah Abdullah, Assistant Minister in the Chief Minister's Department during the launching of the UiTM Sarawak Conference at the university campus in Kota Samarahan on 2 December 2008.